AIDS evolution of an epidemic - Bruce D. Walker, lecturer; Bisola O. Ojikutu, lecturer; Howard Hughes Medical Institute (Chevy Chase, Md. Howard Hughes Medical Institute, 2008)
Two leading AIDS researches discuss the lastest findings on HIV.
Disc 1. Lecture 1: From outbreak to epidemic -- Lecture 2: AIDS and the HIV life cycle -- Lecture 3: Drugs and HIV evolution -- Lecture 4: Vaccines and HIV evolution -- Animations: U.S. AIDS epidemic -- HIV life cycle -- Antigen presentation and CTL -- AZT blocks reverse transcriptase -- protease inhibitor -- Interactive Features: Immunology primer -- What is a retrovirus? -- Adherence and resistance -- Video clips: First AIDS patients -- Rapid AIDS virus test -- Symptoms of acute HIV infection -- CTL killing a target cell -- Benefits of antiretroviral therapy -- Steve Crohn: HIV free despite exposure -- Adhering to an antiretroviral regimen -- Demo: Student adherence activity -- HIV's origin in Africa -- Bob Massie -- Infected but AIDS free -- Disc 2. Discussions: Students fighting the HIV epidemic -- Living with HIV -- Video extras: South Africa feature -- WhizzKids united -- iThemba -- Interviews: Dr. Bisola O. Ojikutu ; Dr. Bruce D. Walker ; Kwame Atsina ; Silvia Caballero ; Tobi Ogbechie ; Katie Walter.
Howard Hughes Medical Institute holiday lectures on science, December 2007.
Keywords: AIDS (Disease).; AIDS (Disease) -- History; AIDS (Disease) -- Epidemiology; AIDS (Disease) -- Treatment; HIV Infections; Acquired Immunodeficiency Syndrome